Digital Literacy Program Management for Reducing Gadget Misuse among Madrasah Ibtidaiyah Students - Siti Masyarafatul Manna Wassalwa; Ainur Rofiq (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Escalating gadget addiction among primary school students constitutes a growing educational challenge in Indonesia, with documented negative effects on learning concentration, academic performance, and psychosocial wellbeing, yet systematic management strategies for digital literacy programmes at Islamic primary schools (madrasah ibtidaiyah) remain underexplored in the empirical literature. This study examined the implementation of digital literacy programme management and its effects on reducing gadget misuse among students at MI Nurul Huda Jebung Lor Tlogosari, Bondowoso, East Java, Indonesia. A qualitative case study design was employed with eleven purposively selected participants comprising the madrasah principal, four teachers, three students (Grades IV–VI), and three parents. Data were collected through in-depth semi-structured interviews, non-participant observation, and document analysis. Thematic analysis followed the Miles–Huberman–Saldaña interactive model; trustworthiness was established through source and technique triangulation and member checking. The findings reveal that the digital literacy programme at MI Nurul Huda operates through a POAC (Planning, Organizing, Actuating, Controlling) management framework integrated with three digital literacy content dimensions time management, digital ethics, and positive technology use alongside social cognitive behavioural principles. Programme implementation produced progressive reductions in gadget addictive behaviour, improved student time discipline, and increased capacity for selective critical digital engagement, but success was contingent on sustained cross-stakeholder collaboration among the madrasah, parents, and community. Four structural challenges limited teacher digital competency, inconsistent parental supervision, infrastructure constraints, and permissive social environment were identified alongside corresponding institutional mitigation strategies. The study contributes an empirically grounded POAC-integrated digital literacy management model applicable to Islamic primary education contexts facing digital transformation pressures, particularly in resource-limited and values oriented rural madrasah settings.